Pemetaan Potensi Wisata Di Kabupaten Pulau Morotai - Gapang, Siti Tarisa; M. Samiun, Muhammad Zais; Kamal, Muhammad; Mala, Said; Amin, Chairullah (CV. ULIL ALBAB CORP, 2024)
Tourism has a huge impact on development when it is well managed, which in its development is adjusted to the mapped potential and always prioritises tourists' perceptions of the tourism services they enjoy. This research aims to identify tourism potential and find out the factors that need to be considered in tourism development based on the perceptions of users of tourism services. The research uses a qualitative approach with descriptive methods so that various phenomena can be explored properly. The results showed that, first, tourism development in Morotai Island Regency has the potential to be carried out in a sustainable manner with various potentials scattered in natural tourism including beach tourism and historical tourism, namely trikora historical tourism, glass water nature tourism, nunuhu beach tourism, nakamura waterfall nature tourism, dodola beach tourism, kokoya beach tourism, jababeka beach tourism. Second, in an effort to develop tourism potential, there are several factors that influence it as the perception of tourism service users, among others, the location factor of attractions that are very attractive to visitors, the attractiveness factor of attractions that are very high but the promotion of attractions that are still low, the accessibility factor is very supportive, and the facility factor is good enough even though there still has to be improvements that need to be made.